2019
DOI: 10.3171/2019.2.focus195
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of full-endoscopic and minimally invasive decompression for lumbar spinal stenosis in the setting of degenerative scoliosis and spondylolisthesis

Abstract: OBJECTIVEThe management of lumbar spinal stenosis (LSS) with concurrent scoliosis and/or spondylolisthesis remains controversial. Full-endoscopic unilateral laminotomy for bilateral decompression (ULBD) facilitates neural decompression while preserving stabilizing osseoligamentous structures and may be uniquely suited for the treatment of LSS with concurrent mild to moderate degenerative deformity. The safety and efficacy of full-endoscopic versus minimally invasive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 54 publications
2
60
1
1
Order By: Relevance
“…Overall revision rate is 1.9%, incidental durotomy rate around 0%-8.6%, transient paresthesia around 2.6%, epidural hematoma and headache each around 1.9%. 3,7,12,[22][23][24][25][26] These complications are comparable in some and favorable in other studies as compared to open and minimally invasive spinal decompression. [27][28][29][30][31] Infection rate is extremely low in minimally invasive surgery.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Overall revision rate is 1.9%, incidental durotomy rate around 0%-8.6%, transient paresthesia around 2.6%, epidural hematoma and headache each around 1.9%. 3,7,12,[22][23][24][25][26] These complications are comparable in some and favorable in other studies as compared to open and minimally invasive spinal decompression. [27][28][29][30][31] Infection rate is extremely low in minimally invasive surgery.…”
Section: Discussionmentioning
confidence: 87%
“…This complication rate was comparable to other similar studies. 25 None of the complications required conversion or revision surgery. Incidental durotomy in our LE-ULBD series was small and only required patch blocking dural repair.…”
Section: Discussionmentioning
confidence: 94%
“…[29][30][31] The benefit extends even to lumbar stenosis cases with spondylolisthesis. 32 Additionally, there are also several studies describing similar favorable results bewww.e-neurospine.org S95 tween microsurgical or tubular techniques of ULBD and endoscopic lumbar decompression in the setting of lumbar stenosis, with shorter hospital stay and less collateral tissue injury. 33,34 It may be reasonable to infer from these reports that endoscopic stenosis decompression can also deliver adequate decompression comparable to ULBD and open laminectomy.…”
Section: Discussionmentioning
confidence: 97%
“…21 With the advancement of surgical technology and the improvement of instruments, several studies have reported favorable results in the treatment of LSS with full-endoscopic ULBD. [22][23][24][25][26] So far, there have been few studies comparing fullendoscopic and microscopic ULBD in the treatment of elderly lumbar spinal stenosis. Thus, the objective of this study was to evaluate the safety and efficacy of fullendoscopic ULBD compared with that of microscopic ULBD for treating elderly lumbar spinal stenosis, who usually has comorbidities such as hypertension, diabetes, and heart disease.…”
Section: Introductionmentioning
confidence: 99%